Mobilisatie + organisatie = renovatie + wederhuisvesting : studie van de renovatie van de Kruidtuinwijk in Sint-Joost-ten-Node - Bozzo, Irma; Matthys, Camille; Martens, Albert (Leuven : KUL, 1992)
BMLIK
Nederlands
Monografie
Keywords: wijkontwikkeling